Losing Track of Lipids in Children and Adolescents with Type 1 Diabetes: Towards Individualized Patient Care - Heyden, Josine C. van der; Birnie, Erwin; Bovenberg, Sarah A.; Dekker, Pim; Veeze, Henk J.; Mul, Dick; Aanstoot, Henk-Jan (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aim To assess 1) the prevalence of children and adolescents with type 1 diabetes (T1D) changing from low-risk into borderline-high-risk lipid levels or from borderline-high-risk into high-risk lipid levels (‘lose track of lipids’) and 2) the power of a risk score including the determinants HbA1c, body mass index (BMI), gender, age, diabetes duration and ethnicity in predicting which patients lose track of lipids.Methods 651 children and adolescents with T1D were included in this longitudinal retrospective cohort study. Lipid dynamics and the impact of the risk score on losing track of lipids were evaluated. Kaplan-Meier analysis was used to estimate screening intervals.Results 31–43% percent of the patients had lost track of one or more lipids at the next lipid measurement. This happened more frequently in patients with a low-risk lipid level at start. Depending on the lipid parameter, 5% of patients with low-risk lipid levels lost track of lipids after 13–23 months. The risk score based on concomitant information on the determinants was moderately able to predict which patients would lose track of lipids on the short term.Conclusions A considerable number of children and adolescents with T1D loses track of lipids and does so within a 2-year screening interval. The predictive power of a risk score including age, BMI, gender, HbA1c, diabetes duration and ethnicity is only moderate. Future research should focus on another approach to the determinants used in this study or other determinants predictive of losing track of lipids on the short term.
Keywords: type 1 diabetes; children; dyslipidemia; HbA1c; longitudinal